Does thyroid function have any relation with components of metabolic syndrome? - Shah, Yash; Vadher, Abhishek; Reddy, Karthik; Chapadia, Harsh (International Journal of Research in Medical Sciences, 2017)
Background: Obesity, insulin resistance, physical inactivity, advanced age and hormonal disturbances have been suggested to be the underlying risk factors for the development of metabolic syndrome. Thyroid dysfunction can cause obesity, and can in turn lead to metabolic syndrome and can also be a cause of lipid abnormalities. Hence we tried to study the effect of thyroid function on the components of metabolic syndrome. Methods: Blood pressure, waist circumferences, HDL cholesterol and triglycerides were measured in all patients. TSH was measured and on its basis patients were divided in three groups: euthyroid, hypothyroid and subclinical hypothyroid. Results: There were 28 females and 22 males. Mean BMI was 31.51±5.21 kg/m2. The mean systolic blood pressure was 139.04±26.67 mm Hg and the diastolic pressure was 88.32±14.95 mm Hg. Mean waist circumference was 102±10.1 cm & mean waist: hip ratio was 0.97±0.094. HDL <50 in males and <40 in females in Euthyroid showed statistical significance (p value 0.05). Other components did not gain a statically significance. Comparing gender wise Subclinical hypothyroidism patients with Euthyroid patients, females having subclinical hypothyroidism are more likely to have metabolic syndrome (p value =0.03). This is not so in case of males. Conclusions: Female patients having subclinical hypothyroidism have higher chances of have metabolic syndrome as compared to males. Euthyroid patients with metabolic syndrome had low cholesterol. Other components of metabolic syndrome had no statically significance with thyroid function.